2015
DOI: 10.1016/j.neuron.2015.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Accumbal D1R Neurons Projecting to Lateral Hypothalamus Authorize Feeding

Abstract: Feeding satisfies metabolic need but is also controlled by external stimuli, like palatability or predator threat. Nucleus accumbens shell (NAcSh) projections to the lateral hypothalamus (LH) are implicated in mediating such feeding control, but the neurons involved and their mechanism of action remain elusive. We show that dopamine D1R-expressing NAcSh neurons (D1R-MSNs) provide the dominant source of accumbal inhibition to LH and provide rapid control over feeding via LH GABA neurons. In freely feeding mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
292
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 257 publications
(326 citation statements)
references
References 63 publications
30
292
3
1
Order By: Relevance
“…These data, together with findings from in vivo DA measurements and cell-ablation studies, suggest that DA levels in DS and NAc, acting via D1R-MSNs, signal the nutritive and gustatory quality of sugar, respectively, and that DS output may serve to prioritize energy seeking over taste quality (Tellez et al, 2016;de Araujo, 2016). Surprisingly, in vivo recordings of NAc D1R-MSNs found that the activity of these neurons reduced during palatable food consumption and, consistent with this observation, noncontingent optogenetic inhibition of NAc D1R-MSNs prolonged food intake (O'Connor et al, 2015). Moreover, lick-contingent and noncontingent optogenetic stimulation of D1R-MSN projections to LH inhibited palatable food intake, even in food deprived mice, suggesting that the NAc D1R-MSN to LH pathway may serve to override immediate metabolic need and allow rapid consumption control in response to changing external stimuli (O'Connor et al, 2015).…”
Section: Striatal Cell Types Controlling Feeding Behaviorsupporting
confidence: 65%
See 4 more Smart Citations
“…These data, together with findings from in vivo DA measurements and cell-ablation studies, suggest that DA levels in DS and NAc, acting via D1R-MSNs, signal the nutritive and gustatory quality of sugar, respectively, and that DS output may serve to prioritize energy seeking over taste quality (Tellez et al, 2016;de Araujo, 2016). Surprisingly, in vivo recordings of NAc D1R-MSNs found that the activity of these neurons reduced during palatable food consumption and, consistent with this observation, noncontingent optogenetic inhibition of NAc D1R-MSNs prolonged food intake (O'Connor et al, 2015). Moreover, lick-contingent and noncontingent optogenetic stimulation of D1R-MSN projections to LH inhibited palatable food intake, even in food deprived mice, suggesting that the NAc D1R-MSN to LH pathway may serve to override immediate metabolic need and allow rapid consumption control in response to changing external stimuli (O'Connor et al, 2015).…”
Section: Striatal Cell Types Controlling Feeding Behaviorsupporting
confidence: 65%
“…Surprisingly, in vivo recordings of NAc D1R-MSNs found that the activity of these neurons reduced during palatable food consumption and, consistent with this observation, noncontingent optogenetic inhibition of NAc D1R-MSNs prolonged food intake (O'Connor et al, 2015). Moreover, lick-contingent and noncontingent optogenetic stimulation of D1R-MSN projections to LH inhibited palatable food intake, even in food deprived mice, suggesting that the NAc D1R-MSN to LH pathway may serve to override immediate metabolic need and allow rapid consumption control in response to changing external stimuli (O'Connor et al, 2015). The contradictory findings between these two studies may reflect further segregation of NAc D1R-MSN function according to projection targeting of the ventral pallidum (Tellez et al, 2016) or LH (O'Connor et al, 2015).…”
Section: Striatal Cell Types Controlling Feeding Behaviorsupporting
confidence: 65%
See 3 more Smart Citations